Ground temperatures, landforms and processes in an Atlantic mountain. Cantabrian Mountains (Northern Spain) - Pisabarro Pérez, Alfonso; Pellitero Ondicol, Ramón; Serrano Cañadas, Enrique; Gómez Lende, Manuel; González Trueba, Juan José (CATENA, 2017)
Producción Científica Ground temperatures determine significant geomorphological processes in a wet and temperate mountain with a narrow high elevation range belt. Twenty five temperature data loggers were buried at a shallow depth in different locations and altitudes and at specifically cold locations at two massifs in the Cantabrian Mountains (North Spain), Picos de Europa and Fuentes Carrionas. This paper analyses the ground thermal regime and associated parameters (e.g. freeze index, duration and depth of freeze, freeze and thaw cycles) and correlates them with active geomorphological processes and landforms. The thermal regime varies in accordance to the topoclimatic conditions, and it was possible to determinate annual phases in function of snow cover behaviour. Main active processes and landforms stop their activity with a large snow cover which thermally protects the ground and in consequence, avoids the freeze and thaw cycles. During this period, the records allow to asseverate the evidence of seasonal freeze grounds in several locations. Permafrost was not discover on the ground at any of the thermometers except one located at the vicinity of a relict ice patch. With the help of geomorphological maps and previous works, we got to establish the relation between geomorphological processes, landforms, snow cover and ground thermal regime. Ministerio de Educación y Formación Profesional (project FPU13/05837) Organismo Autónomo Parques Nacionales - Ministerio de Agricultura y Pesca, Alimentación y Medio Ambiente (project OAPN 053/2010) Ministerio de Economía, Industria y Competitividad (project CGL2015-68144-R) Leverhulme Trust International Network (grant IN-2012-140)